Gertrude Stein and the making of Jewish modernism - Feinstein, Amy (Gainesville : University Press of Florida, 2020)
"Challenging the assumption that modernist writer Gertrude Stein seldom integrated her Jewish identity and heritage into her work, this book uncovers Stein's constant and varied writing about Jewish topics throughout her career. Amy Feinstein argues that Judaism was central to Stein's ideas about modernity, showing how Stein connects the modernist era to the Jewish experience"--
Introduction: The Stein Era -- An Israel of the Imagination: The Sciences of Race, Matthew Arnold, and Stein's Modern Jew -- Brother Singulars: The "Hidden Tradition" of Jewish Culture in Stein's First Fictions -- "So much like a yid:" An Associative Genealogy of Jewish Types in the Notebooks for The Making of Americans -- Pariah Modernism: Estranging Narration in The Making of Americans -- "Can a Jew be wild": A Radical Jewish Grammar in the Voices Poems -- "Everybody can persecute anybody": What's Funny about Jewish identity in Wars I Have Seen -- Conclusion: Making Sense of a Sensationally Jewish Stein
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 07, 2020).
eBooks on EBSCOhost
Keywords: Stein, Gertrude, -- 1874-1946 -- Criticism and interpretation; Stein, Gertrude, -- 1874-1946 -- Literary style; Stein, Gertrude, -- 1874-1946; Modernism (Literature); Jews in literature; Modernisme (Littérature); Juifs dans la littérature.; Jews in literature; Literary style; Modernism (Literature); Electronic books; Criticism, interpretation, etc